Effect of Different Impression Techniques on Marginal Fit of Restoration – An In Vitro Study - Priyanka S. Raghav; S Abirami; Abhinav Gupta; Faiz Noor Khan Yusufi; Shaista Afroz (Indian Journal of Dental Research)
Introduction: Impression making is one such important clinical step, which is critical in the accurate fitting of resulting prostheses. Impression making itself depends on the type of material and the impression technique used to record the details. Various combinations of material and the technique have been described in the literature. Aim: To evaluate the effect of three different impression techniques on the marginal fit of computer-aided designed/computer-aided manufactured (CAD/CAM) single unit composite fixed dental prostheses (FDP), different consistencies of addition silicone impression material and different tray design were utilized. Method: Impression of prepared tooth on typodont was made using Matrix impression system, two-step putty wash technique, and individual tooth tray technique. Prosthesis was fabricated using CAD/CAM technology and marginal accuracy was evaluated using scanning electron microscopy (SEM). Result: In the present study, the matrix impression system resulted in less microgap in both mid-buccal and mid-mesial region, whereas putty wash technique showed very high standard deviation in the interproximal region. Conclusion: Matrix impression system had the best results at both mid-buccal and mid-mesial position with least marginal discrepancy. Clinical Implication: The findings of this study could be used by clinicians to help them choose the viscosity of polyvinylsiloxane material and impression techniques for FDP that will result in high-accuracy impressions and well-fitting prostheses.